Why is the clinical response to cardiac resynchronization better in LBBB patients?. (18th September 2020) - Kvasnička, Jiří; Havlíček, Aleš; Bělohlávek, Jan; Večeřa, Jan; Čermáková, Eva
Abstract: Aims: The improved clinical response in patients with left bundle branch block (LBBB) over LBBB‐free patients treated with cardiac resynchronization therapy with a defibrillator (CRT‐D) is commonly attributed to an LBBB abnormality. We aimed to find an alternative explanation. Methods and results: We analysed an immediate effect of selecting the LBBB group of patients in a cohort of 63 non‐ischaemic cardiomyopathy (non‐ICM) and 83 ischaemic cardiomyopathy (ICM) patients treated with CRT‐D; 75% of non‐ICM and 51% of ICM patients had an LBBB abnormality on the electrocardiogram, with a significant difference ( P = 0.0032 by χ 2 ). As a result of this difference, the proportion of non‐ICM patients increased from 43% in the primary cohort to 53% in LBBB selection and decreased to 28% in non‐LBBB group. By nonparametric survival analysis, the hazard ratio in non‐ICM patients in the LBBB selection decreased from 0.48 ( P = 0.0488) to 0.36 ( P = 0.0251) and increased in the non‐LBBB group to 0.75 ( P = 0.6496). Any comparison of LBBB and non‐LBBB groups must compare sets with a significantly altered proportion of patients of different aetiologies. Most publications on LBBB patients are erroneous because they compare LBBB with non‐LBBB groups, not taking into account that the groups have been substantially changed by the selection process. Conclusions: The declared outcome of the LBBB groups reflects inevitably the survival outcome of their non‐ICM patients and not the intended outcome of patients with LBBB. CRT‐D in patients with different aetiologies of cardiomyopathy calls for separate evaluation.